2017
DOI: 10.1016/j.jcv.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eMAG™ versus NucliSENS® EasyMAG® performance on clinical specimens

Abstract: The two platforms showed comparable performance on the types of clinical specimen tested. With higher automation and throughput than easyMAG, the eMAG™ platform is likely to be advantageous for laboratories performing a large number of molecular analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These differences could be due to the various properties of viruses, including the presence of an envelope, the type of genome, or the size of the virions. Yang et al showed a better performance of RNA virus recovery with EasyMag (identical silica extraction technology and similar performance to that of Emag [ 45 ]) compared to the MagNA Pure Compact. They explained this difference by a possible RNA degradation or by an ineffective binding of RNA to the magnetic beads [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be due to the various properties of viruses, including the presence of an envelope, the type of genome, or the size of the virions. Yang et al showed a better performance of RNA virus recovery with EasyMag (identical silica extraction technology and similar performance to that of Emag [ 45 ]) compared to the MagNA Pure Compact. They explained this difference by a possible RNA degradation or by an ineffective binding of RNA to the magnetic beads [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total nucleic acid was extracted using the NucliSens EASYMAG system (Marcy l’Etoile, France). 9 , 10 We used reverse transcriptase quantitative PCR to identify RSV following the protocol developed by the respiratory viruses branch at the US Centers for Disease Control and Prevention (CDC). 11 We tested each sample for the constitutive human enzyme RNAseP to show adequate sampling and the absence of PCR inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, with minor or no differences in the LOD, all three platforms presented very similar performance. As the three platforms are technically similar, especially eMAG and easyMAG, these analytical assessments were expected as previously described [9].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the semi-automated easyMAG system has been extensively investigated; the platform was shown to efficiently extract viral nucleic acid [7,8]. In a study that compared the performance of the new eMAG and the easyMAG systems, eMAG was shown to perform equally well on several types of clinical samples including respiratory samples [9]. However, no large-scale study has simultaneously compared the performance of the eMAG to that of easyMAG and MagNA PURE 96 in nucleic acid extraction from respiratory samples.…”
Section: Introductionmentioning
confidence: 99%